ANALYSIS OF MARKETING MANAGEMENT IN INCREASING SAVING PRODUCTS IN KSPPS BMT NU, MLANDINGAN BRANCH, SITUBONDO - Sofian Syaiful Rizal; Mamik Sari Dewi (JURNAL PROFIT, 2021)
Marketing management is the key to the continuity of an organization’s business so that it runs according to its function. The development of financial institutions, both banks, and non-banks, will encourage financial institutions always to optimize their marketing activities. Analyzing the market and its environment to find out how big the opportunity is to seize the market and how big the threat is that must be faced. This article aims to find out how marketing management is in improving products at the BMT NU Mlandingan branch. This study uses a descriptive qualitative method by conducting structured interviews in the form of questions related to obtaining relevant informants from customers and employees of the BMT NU Mlandingan Branch. Marketing management process by doing market segmentation, target market, determination, positioning, and differentiation. Savings and financing products are good and increasing from the intensity of increasing the number of customers with the reason that customers are easier and understand the advantages of savings and financing products at the malandingan branch of BMT NU. The findings in this study indicate that promotions can increase the number of customers in a faster time and reach a wider audience using existing media. Keywords: Marketing management, Products, BMT